Edukasi dan Pendampingan Mitigasi Bencana Tanah Longsor bagi Masyarakat Kelurahan Leato Utara, Kota Gorontalo - Anton Kaharu; Faiza A. Dali; Satar Saman; Kasmat Saleh Nur; Berni Idji; Mohamad Faisal Dunggio (Yayasan Daarul Huda Kruengmane, 2025)
Leato Utara Sub-district, Gorontalo City, is an area with a high level of landslide hazard due to its hilly topography, steep slopes, and relatively high rainfall intensity. The main problem faced by the community is the low level of knowledge and preparedness in dealing with potential landslide disasters. This Community Service Program (CSP) aims to enhance community knowledge, awareness, and capacity in landslide disaster mitigation through education and assistance activities. The implementation methods include disaster mitigation counseling, participatory discussions, preparedness simulations, and mentoring in the formulation of simple mitigation measures based on local conditions. The target beneficiaries are residents living in landslide-prone areas of Leato Utara Sub-district. The results indicate an improvement in community understanding of the causes, early warning signs, and mitigation measures for landslides, as well as increased community preparedness in responding to potential disasters. In addition, the establishment of a shared understanding regarding preventive actions and emergency response serves as an indicator of the program’s success. This community service activity is expected to contribute to the development of a more resilient and disaster-prepared community in Leato Utara Sub-district, Gorontalo City.